2015
DOI: 10.2514/1.a32894
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stability Analysis of Blunt-Body Entry Vehicles Using Time-Lagged Aftbody Pitching Moments

Abstract: This analysis defines an analytic model for the pitching motion of blunt bodies during atmospheric entry. The proposed model is independent of the pitch-damping sum coefficient present in the standard formulation of the equations of motion describing pitch oscillations of a decelerating blunt body, instead using the principle of a time-lagged aftbody moment as the forcing function for oscillation divergence. It is shown that the dynamic oscillation responses typical to blunt bodies can be produced using hyster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This "phase lag" phenomenon has been cited as one of the mechanisms of dynamic instability in entry capsules. For a more detailed treatment of this theory, the reader is referred to the work of Abe et al, 3 Teramoto et al, 4 and Kazemba et al 5 For the current analysis it is sufficient to say that, based on this theory, the greater the phase offset, and the greater the amplitude of the backshell moment, the greater will be the instability. Comparing the two plots, we do not see significant difference in the extent of phase lag between the two codes.…”
Section: Forebody and Backshell Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This "phase lag" phenomenon has been cited as one of the mechanisms of dynamic instability in entry capsules. For a more detailed treatment of this theory, the reader is referred to the work of Abe et al, 3 Teramoto et al, 4 and Kazemba et al 5 For the current analysis it is sufficient to say that, based on this theory, the greater the phase offset, and the greater the amplitude of the backshell moment, the greater will be the instability. Comparing the two plots, we do not see significant difference in the extent of phase lag between the two codes.…”
Section: Forebody and Backshell Momentsmentioning
confidence: 99%
“…1,2 The current ballistic range campaign will provide unique data for comparison to CFD predictions in that the ballistic range models will be instrumented with pressure transducers, enabling greater resolution of the forebody and aftbody contributions to the total aerodynamic forces. Additionally, pressure transducers located on the model backshell will allow comparison of the predicted wake flow environment, which is believed to have a significant effect on the dynamic stability of blunt bodies in the low-supersonic to transonic regime, [3][4][5] to that of the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…In the free-flight test results of the Hayabusa-type and wind tunnel test results, despite variations in some conditions, reports indicated that the frequency changed, while the AOA amplitude remained relatively consistent. Abe et al (2000) and Kazemba et al (2015) extended the Hiraki model to account for the phase delay, thereby allowing for an assessment of how the phase delay influenced the parameters of the model. Additionally, coupled analyses (Takeda et al, 2020;Yang et al, 2016;Stern et al, 2012) with fluid and motion were used to simulate wind tunnel test results and improve understanding of dynamic instability.…”
Section: Introductionmentioning
confidence: 99%
“…Hiraki et al 2,3) developed a model equation for the aerodynamic force based on the van der Pol equation. Abe et al 4) and Kazemba et al 1,5) established model equations introducing phase delay effects called "temporal delay" and "lag time factor," respectively, with that of Abe et al being an extended Hiraki model. Although these model equations reproduced well most of the pitch-angle oscillations in the experiments, the third harmonics of the pitching moment was not sufficiently discussed.…”
Section: Introductionmentioning
confidence: 99%